Hand and Foot Surgery Rates in Rheumatoid Arthritis Have Declined From 1986 to 2011, but Large‐Joint Replacement Rates Remain Unchanged: Results From Two UK Inception Cohorts. Issue 5 (May 2014) - Nikiphorou, Elena; Carpenter, Lewis; Morris, Stephen; MacGregor, Alex J.; Dixey, Josh; Kiely, Patrick; James, David W.; Walsh, David A.; Norton, Sam; Young, Adam
<x xml:space="preserve">Abstract</x> Objective To assess whether there have been any secular changes in orthopedic interventions in patients with rheumatoid arthritis (RA) since 1986, as examined in 2 early rheumatoid arthritis (RA) inception cohorts with up to 25 years of followup. Methods The study examined orthopedic data from the UK Early RA Study (1986–1999, 9 centers; n = 1, 465) and the UK Early RA Network (2002–2012, 23 centers; n = 1, 236) with linkage to national data sets (Hospital Episode Statistics, National Joint Registry, and Office of National Statistics). Clinical and laboratory measures and hand and foot radiographs were standardized and obtained yearly in both cohorts. The use of disease‐modifying antirheumatic drugs (DMARDs), corticosteroids, and biologic therapies reflected the contemporary conventional practices and guidelines of the time frames examined. Recruitment years were grouped into 6 periods, and interventions were classified into major, intermediate, and minor categories. Results A total of 1, 602 orthopedic surgical procedures were performed in 770 patients (29%) over a maximum of 25 years of followup. The 25‐year cumulative incidence rate of major interventions was 21.7% (range 19.4–24.0%), and that of intermediate interventions was 21.5% (range 17.8–25.5%). There was a decline in the 10‐year cumulative incidence of intermediate surgeries over time (P < 0.001), but not of major/minor surgery. This decline coincided with a gradual shift from sequential monotherapy to combination DMARD therapies and biologic agents in recent recruitment periods. Conclusion Orthopedic surgery is an important and common outcome in RA. Only the rates of hand/foot surgery showed a consistent decline from 1986 to 2011. Possible explanations include differences in the pathophysiologic processes affecting the joints, variations in the responses to therapy between large‐joint and small‐joint destructive processes, and changes in service provision and thresholds for surgery over time.